Tuberculosis vaccines: progress and challenges. - Checkley, A; Mcshane, H (2011)
An effective tuberculosis (TB) vaccine could have a significant impact on the current TB pandemic. The past decade has seen sustained global investment into reaching this goal; currently there are several promising vaccines in clinical trials. Current strategies include the development of an improved bacille Calmette-Guerin (BCG) vaccine to be given at birth and a booster vaccine to be administered after BCG. Here, we describe the current vaccination strategy and review the main issues in novel TB vaccine development. Potential vaccine candidates are evaluated in pre-clinical animal models, and the most promising go into clinical testing; a vaccine candidate is evaluated in at least one model before progressing to early clinical trials. The main challenge in early trials is the lack of a defined correlate of vaccine-induced immune protection. Following this, large efficacy trials are undertaken, which face the daunting challenges of cost, logistics and trial site capacity.